Life lessons after a career in intensive care medicine (Paliativní medicína, 2022)
Reprinted by permission from Springer Nature: Springer, Intensive Care Medicine. J. Randall Curtis. Life lessons after a career in intensive care medicine, 2021 Springer-Verlag GmbH Germany https://doi.org/10.1007/s00134-021-06567-z